(3GdeMUhd aj Yde GdCUhds - (3GdCYQLj, GdMSjfj, GdcGXej, eMSf Hf MSf Hf GdeQJVi, J(B1227(3g`s
(3ChdgG (B:s
(3GdMeO ddg (B...(3bgPG gh Gdaf GdKGfj ef cJGH GdeMUhd (B..(3hjTJed Ydi NeSI CHhGH ; GdGhd aj GdcJGH GdeLjO , GdKGfj aj GdSfI GdZQGA , GdKGdK aj Odjd GdYbd GdQGLM EdjgeG , GdQGHY aj ELeGY GdWGFaI GdeMbI (B...s
(3BNQgG (B:s
... (3OYhi Gf YQhV GdCMhGd cja cGfJ JefY ef GdMce HGSJeQGQ GdCMcGe MJi jbhe GdOdjd Ydi GdYOe hefg jXgQ Cfg dG jbJU HGdefY Ydi GSJUMGH Mce GdLeGYI hbhdg (B: (3hHeKd Pdc fLjH EdN jQjO Gf GdbWY HGSJeQGQ GdhLhO aj eKd (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\286s
(3EjVGM Gdecfhf (B2\443s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs